Reach and impact of a nationwide media campaign in Ethiopia for promoting safe breastfeeding practices in the context of the COVID-19 pandemic - Abel Negussie; Bereket Tefera; Elyas Melaku Mazengia; Ariam Hailemariam; Ephrem Lejore; Tariku Dejene; Abiy Tefera; Ramadhani Noor; Stanley Chitekwe; Hiwot Getachew; Rachana Sharma; Eshetu Girma (BMC, 2024)
Abstract Background In response to the COVID-19 challenge and the consequent concerns and misconceptions about potential mother-to-child virus transmission, the United Nations Children's Fund (UNICEF), in collaboration with the Ethiopian Ministry of Health, launched a 3-month nationwide media campaign to promote appropriate and safe breastfeeding practices using national and regional television and radio channels, as well as social media. This study assesses the reach and impact of a media campaign in Ethiopia on improving mothers', partners'/caregivers', and the public's awareness of and practices related to appropriate and safe breastfeeding. Methods A two-round mobile survey was conducted using random digit dialing (RDD) and an interactive voice response (IVR) system. In order to assess the impact of the media campaign, the study compared outcomes related to awareness, perceptions, and safe breastfeeding practices using post-intervention comparison data across levels of exposure (exposed vs. unexposed to the campaign). A propensity score matching (PSM) analysis was performed using a two sample test of proportions to estimate the impact of the media campaign. Results Among the 3170 mobile subscribers who completed the survey questions, half (50%) reported that they had seen or heard media advertisements about appropriate breastfeeding, the importance of continuing breastfeeding during the COVID-19 pandemic, and how to safely breastfeed a baby when a mother is suspected or confirmed with COVID-19. The PSM analysis showed that exposure to the media campaign was significantly associated with awareness and perceptions of the importance of continuing appropriate breastfeeding during the pandemic among the general public (proportion difference, 0.16; 95% CI, 0.12-0.19; p < 0.0001) and mothers with children under 2 years old or their partners (proportion difference, 0.06; 95% CI, 0.01-0.12, p = 0.01). Conclusions The nationwide media campaign promoting safe breastfeeding practices in the context of COVID-19 reached half of the target breastfeeding mothers and the general public and had a significant impact on awareness and perceptions about the importance of continuing appropriate and safe breastfeeding practices. Future media campaigns should ensure that the intensity and frequency of media spots are appropriate to achieve adequate exposure, message recall, and influence infant and young child feeding behaviors.